Al-Suyuti Dan Kontroversi Strata Ijtihad: Telaah atas Klaim Mujtahid Mutlaq al-Suyuti dan Landasan Normatifnya - Ahwan Fanani (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2008)
The 6th century of Islam witnessed the first emergence of the new class of ulama that tended to